Audit Committee Non-Existing Reasons’: Evidence of Iran - Salehi, Mahdi (Mediterranean Journal of Social Sciences, 2011)
The audit committee’s responsibility to effectively oversee the integrity of the financial reporting process has become a mandate of the capital markets in the aftermath of the sweeping changes affect corporate governance. However, in Iran it is not mandatory to Iranian corporation to conducting audit committee. The results of current study shows that the major reason for non-existing audit committees is individualism culture among the Iranian audit practitioners, centralization trend of Iranian managers, and lack of legal force respectively.